Roles of the gut microbiota in human neurodevelopment and adult brain disorders - Rahul Mallick; Sanjay Basak; Ranjit K. Das; Antara Banerjee; Sujay Paul; Surajit Pathak; Asim K. Duttaroy (Frontiers in Neuroscience)
Growing evidence demonstrates the connection between gut microbiota, neurodevelopment, and adult brain function. Microbial colonization occurs before the maturation of neural systems and its association with brain development. The early microbiome interactions with the gut-brain axis evolved to stimulate cognitive activities. Gut dysbiosis can lead to impaired brain development, growth, and function. Docosahexaenoic acid (DHA) is critically required for brain structure and function, modulates gut microbiota, and impacts brain activity. This review explores how gut microbiota influences early brain development and adult functions, encompassing the modulation of neurotransmitter activity, neuroinflammation, and blood-brain barrier integrity. In addition, it highlights processes of how the gut microbiome affects fetal neurodevelopment and discusses adult brain disorders.